High prevalence and pathogenicity of Cryptosporidium serpentis in snakes in southern China - Falei Li; Xinrui Wang; Lihua Xiao; Yaoyu Feng; Yaqiong Guo (Current Research in Parasitology and Vector-Borne Diseases)
In southern China, snakes have cultural and economic significance, serving both as traditional dietary resources and as increasingly popular pets. However, the prevalence and clinical impacts of Cryptosporidium spp. in snakes in southern China remain poorly understood. Between April 2018 and September 2020, we collected 357 fecal samples from wild snakes, farmed snakes, and pet snakes in Hunan and Guangdong, two provinces in southern China. Cryptosporidium spp. were identified and subtyped by sequence analyses of the small subunit rRNA (SSU rRNA) gene and the 60 kDa glycoprotein (gp60) gene, respectively. The intensity of oocyst shedding in Cryptosporidium-positive samples was evaluated using SSU rRNA-LC2 quantitative PCR. Histological examinations of gastric tissues from infected pet snakes were conducted to assess potential parasite-induced pathology. Overall, 93 of 357 (26.1%) samples were positive for Cryptosporidium spp., and the detection rates were 17.0%, 31.4%, and 46.2% in farmed snakes, pet snakes, and wild snakes, respectively. Five species of Cryptosporidium were identified, including C. serpentis (n = 77), C. tyzzeri (n = 6), C. varanii (n = 4), C. muris (n = 3), and C. parvum (n = 2). Only C. tyzzeri isolates were subtyped successfully and belonged to IXa subtype family. The highest average number of oocysts per gram (OPG) of feces was observed in C. serpentis samples (4.6 ± 1.7 logs), followed by C. varanii (3.5 ± 0.4 logs), C. tyzzeri (3.3 ± 1.0 logs), C. parvum (3.2 ± 0.4 logs), and C. muris (2.1 ± 1.7 logs). In pet snakes infected with C. serpentis, the gastric mucosal epithelial cells were heavily colonised by the parasites, resulting in significant damage to the villus structure. The results of this study indicate that C. serpentis is prevalent in snakes in southern China and has significant pathogenicity to snakes.